Animation In Hadith Prohibition Maqasid Syariah Perspective - Karlin Permata Suri; Yusdani Yusdani; Hamidullah Marazi (International Tatho Academics, 2024)
Conveying messages through the medium of an animated video in today's life has become a necessity. However, there are still pros and cons to animation as a medium. One of them is the Islamic religious view of this work because it is related to drawing behavior. This situation creates a dilemma for animators because on the one hand, this job is a job that is quite in demand with relatively high pay, while on the other hand, work as an animator is more related to drawing activities because in a hadith there is a prohibition against drawing. This article focuses on what is the role and function of animation in human life today? How does animation serve various positive purposes in various aspects of human life today from a maqasid sharia perspective? The important conclusion of this article is that animation provides a number of benefits in maintaining and applying maqasid sharia because it has great power to influence human thoughts currently using visual-based technology. Whereas animator is a profession that provides benefits in the field of visual-based Islamic education and preaching, 3. Understanding the hadith which prohibits drawing living creatures needs to be reinterpreted in the context of Muslim life today.